Writing on the job : best practices for communicating in the digital age - Coven, Martha B., 1972- (Princeton, NJ : Princeton University Press, 2022)
"Based on her course at the Princeton University School of Public and International Affairs, Martha Coven presents a crisp, brief, up-to-date introduction to clear and compelling writing for future professionals. Coven covers the basics of developing a professional style and writing and revising first and successive drafts. She then covers common types of professional writing, including correspondence, memos, proposals, plans, and reports, critical feedback and cover letters. Incorporating the growing significance of statistics and other quantitative values in professional prose, Coven then turns to writing about numbers, data visualization, and slide decks. And reflecting the need for professionals to address public audiences, she concludes with coverage of instructions and forms, writing for the media, commentary, and public speaking. Coven offers advice with concrete examples and templates. She also provides guidance on how formal or informal to allow your language to be, and how to strike the right tone so your message gets heard. Coven emphasizes the "Bottom Line Up Front" approach used by the U.S. military to ensure efficient communications, by which she stresses the importance of beginning with your big idea or claim. The book stresses how a clear communications culture improves the functioning of any organization"--
"A practical and compact guide to writing for professionalsWriting is an essential skill in today's workplace. From messaging platforms and social media to traditional forms of communication like memos and reports, we rely on words more than ever. Given how much reading we do on mobile devices, being able to write succinctly is critical to success. Writing on the Job is an incisive guide to clear and effective writing for professionals.Martha Coven begins with the basics, explaining how to develop a professional style, get started on a piece of writing, create a first draft, and edit it into a strong final product. She then offers practical advice on more than a dozen forms of writing, from emails and slide decks to proposals and cover letters. Along the way, Coven provides a wealth of concrete examples and simple templates that make the concepts easy to understand and apply.Based on Coven's popular writing classes and workshops at Princeton University as well as her decades of experience in the public and private sectors, Writing on the Job addresses the real challenges professionals face in today's digital age, and shares essential practices that can improve the performance of any organization"--
The basics -- Developing a professional style -- Getting started -- Writing a first draft -- Editing -- Common types of business writing -- Correspondence -- Memos -- Proposals, plans, and reports -- Critical feedback -- Resumes and cover letters -- Numbers and visuals -- Writing about numbers -- Data visualizations -- Slide decks -- Writing for public audiences -- Instructions and forms -- Writing for media -- Commentary -- Public speaking.
Includes bibliographical references and index.
Keywords: BUSINESS WRITING; BUSINESS COMMUNICATION